Experimental study of ice accumulation in unsaturated clean sand. Issue 3 (30th April 2018) - Teng, J.; Shan, F.; He, Z.; Zhang, S.; Zhao, G.; Sheng, D.
Abstract : A series of laboratory experiments is carried out to replicate moisture accumulation in an unsaturated coarse-grained soil underneath an impervious cover. The results show that significant moisture accumulation occurs in relatively dry specimens when the temperature at the cover drops below the freezing point. The tested soil is a coarse-grained sand and is not expected to generate much moisture accumulation according to existing frost susceptibility criteria in the literature. The primary mechanism of moisture migration in the soil is observed to be vapour diffusion, and the primary mechanism of moisture accumulation is ice formation by way of vapour–ice desublimation. It is also observed that two peak values exist along the total water content profile of the 13·5 cm long specimen. For a non-freezing condition, water content gradually decreases from the warmer end to the colder end without any peak value, and the amount of moisture accumulation is less than occurs under freezing conditions. The test results are considered to be useful for understanding vapour diffusion in unsaturated freezing soils, and for validating theoretical and numerical models.